Mitophagy and immune infiltration in vitiligo: evidence from bioinformatics analysis - Luo, Lingling; Zhu, Jing; Guo, Youming; Li, Chengrang (Frontiers in Immunology, 2023)
Background: Vitiligo is an acquired, autoimmune, depigmented skin disease with unclear pathogenesis. Mitochondrial dysfunction contributes significantly to vitiligo and mitophagy is vital for removing damaged mitochondria. Herein, using bioinformatic analysis, we sought to determine the possible role of mitophagy-associated genes in vitiligo and immune infiltration. Methods: Microarrays GSE53146 and GSE75819 were used to identify differentially expressed genes (DEGs) in vitiligo. The mitophagy-related DEGs were then discovered by crossing vitiligo DEGs with mitophagy-related genes. Functional enrichment and protein-protein intersection (PPI) analyses were conducted. Then, the hub genes were identified using two machine algorithms, and receiver operating characteristic (ROC) curves were generated. Next, the immune infiltration and its connection with hub genes in vitiligo were investigated. Finally, the Regnetwork database and NetworkAnalyst were used to predict the upstream transcriptional factors (TFs), microRNAs (miRNAs), and the protein-compound network. Results: A total of 24 mitophagy-related genes were screened. Then, five mitophagy hub genes (GABARAPL2, SP1, USP8, RELA, and TBC1D17) were identified by using two machine learning algorithms, and these genes showed high diagnostic specificity for vitiligo. The PPI network showed that hub genes interacted with each other. The mRNA expression levels of five hub genes were validated in vitiligo lesions by qRT-PCR and were compatible with the bioinformatic results. Compared with controls, the abundance of activated CD4+ T cells, CD8+ T cells, immature dendritic cells and B cells, myeloid-derived suppressor cells (MDSCs), gamma delta T cells, mast cells, regulatory T cells (Tregs), and T helper 2 (Th2) cells was higher, but the abundance of CD56 bright natural killer (NK) cells, monocytes, and NK cells was lower. Correlation analysis revealed a link between hub genes and immune infiltration. Meanwhile, we predicted the upstream TFs and miRNAs and the target compounds of hub genes. Conclusion: Five hub mitophagy-related genes were identified and correlated with immune infiltration in vitiligo. These findings suggested that mitophagy may promote the development of vitiligo by activating immune infiltration. Our study might enhance the comprehension the pathogenic mechanism and offer a treatment option for vitiligo.